REVENUES AND EXPENSES OF THE NATIONAL CENTER FOR CONSTRUCTION LABORATORIES FOR THE YEAR 2021 (World Economics and Finance Bulletin, 2024)
The key to the true success of any institution or government department lies in the degree of interconnection between the administration and the employees of that department and each employee’s knowledge of his responsibility towards his second home (the institution to which he belongs) and his keenness to perform the tasks entrusted to him with precision and honesty. So, This research aims primarily to identify the administrative and financial department and the tasks assigned to the National Center for Construction Laboratories in detail, in addition to the statement of financial position for 2021, which includes revenues and expenses. The research reached a set of conclusions, the most important of which are: There is a discrepancy in revenues, as the increase in revenues for some laboratories is due to the nature of the work environment in that governorate, the size and diversity of projects, and the construction movement in it, in addition to the direction of the local administration in that governorate, which imposes reliance on reputable government agencies about construction inspections for existing projects. In that governorate, it refused to rely on private (private) examining bodies. As for laboratories with low revenues, this is due to the governorate councils' directive to rely on private (private) laboratories and university laboratories to conduct the examination
Keywords: Revenues; expenses; Organizational Chart; Laboratory equipment